On the Essence of Forensic Expert’s Specialized Knowledge and Feasibility of Its Differentiation - B. M. Bishmanov; G. G. Omel’yanyuk (Теория и практика судебной экспертизы, 2024)
The article presents an analysis of the terms «knowledgeable persons» and «forensic expert». Based on the historical analysis of the activities of the «knowledgeable persons» figure and the «expert» figure, a logical sequence of concepts has been established: knowledge – science – knowledgeable persons – knowledgeable persons’ specialized knowledge – expert knowledge – forensic expert’s specialized knowledge – specialized knowledge in an expert specialty – a forensic expert. The authors consider the criteria for differentiating forensic expert’s specialized knowledge into: «expert knowledge», «forensic expert knowledge», «specialized knowledge in an expert specialty». They also propose to distinguish «specialized knowledge» as a legal category. In this case, «forensic expert’s specialized knowledge» is seen as expert knowledge as a result of obtaining forensic expert education and experience in conducting forensic examinations within the framework of its specific type, as well as specialized knowledge in an expert specialty (a specific expert specialty is indicated), which should be understood as expert knowledge, skills and abilities acquired during the development of a specific expert specialty and the subsequent acquisition of professional experience in the production of forensic examinations of a specific type. The feasibility of differentiating forensic expert’s specialized knowledge is analyzed, considering the type of forensic examination in which he specializes. A classification of the names of forensic experts is proposed based on differences in the expertise required to produce a certain kind of forensic examinations.